Teori Ring Structure Raimond Farrin dan Aplikasinya pada Q.S. Al-Baqarah - Ahmad Solahuddin (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2021)
Many scholars are confused with the structure of the Koran. In fact, Bell states that the Qur'an needs to re-arrangement because its structure is unstructured. However, that is what later became an attraction for Islamic studies scholar, which denied the Bell thesis and found the structure of the Koran. Next, the study of the structure of the Qur'an is growing rapidly. The final theory of this study is the ring structure theory developed by Raimond Farrin. This paper will focus on discussing Farrin's ring structure theory applied in Sura al-Baqarah. In the end, the authors conclude: Farrin is a scholar in the field of Arab studies who focus on studying classical, middle Arabic literature and the Koran by using ring structure theory. The ring structure theory follows the structuralism paradigm developed by F. De Saussure. The basic assumption of this theory is that humans have an instinct for strucuture, as well as in literature or the like. For literary works, even scripture, structure is important to understand, because meaning is based on this structure. Next, Structure text refers to three models: parallesime (ABAB), Chiasm (ABBA) and concentrisme (ABCBA). In the end, Farrin managed to find the ring in Q.S. al-Fātiḥah, al-Baqarah, al-Anfal, al-Taubah, al-Rahman and al-Nas.[Banyak sarjana yang bingung dengan struktur al-Qur’ān. Bahkan, Bell pada akhirnya menyatakan bahwa al-Qur’ān butuh ditata ulang karena strukturnya tidak terstruktur. Namun, hal itulah yang kemudian menjadi daya tarik bagi sarjana studi Islam, yaitu membantah thesis Bell dan menemukan struktur al-Qur’ān. Berikutnya, studi mengenai struktur al-Qur’ān pun berkembang pesat. Adapun teori terakhir dari studi ini adalah teori ring structure yang dikembangkan oleh Raymond Farrin. Tulisan ini akan fokus untuk mengulas teori ring structure Farrin yang diaplikasikan dalam surat al-Baqarah. Pada akhirnya, penulis menyimpulkan: Farrin adalah sarjana dalam bidang Arab studies yang fokus mengkaji susastra Arab Klasik, pertengahan dan al-Qur’ān dengan menggunakan teori ring structure. Teori ring structure sesungguhnya mengikuti madzhab structuralisme yang dikembangkan oleh F. De Saussure. Asumsi dasar dari teori ini adalah: bahwa manusia memiliki naluri terhadap strucuture, begitu juga dalam bersastra atau sejenisnya. Untuk karya sastra, bahkan kitab suci, structure adalah hal penting untuk difahami, karena makna didasarkan pada structure ini. Berikutnya, Structure teks mengacu pada tiga model: parallesime (ABAB), Chiasm (ABBA) dan concentrisme (ABCBA). Pada akhirnya, dalam studinya Farrin berhasil untuk menemukan ring dalam Q.S. al-Fātiḥah, al-Baqarah, al-Anfal, al-Taubah, al-Rahman dan al-Nas.]